FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA HIPOTENSI INTRADIALISIS PADA PASIEN GAGAL GINJAL KRONIK DI RUANGAN HEMODIALISIS MELATIRSUP PROF DR. R. D. KANDOU MANADO - Natalia Nova Tampah; Gresty Masi; Muhamad Nurmansyah (JURNAL KEPERAWATAN, 2023)
Backgroud One of the most frequent complications in patients with hemodialysis is an intradialysis hypotension. Some conditions of patients who can trigger a drop in blood pressure during hemodialysis: age, gender, comorbidities such as diabetes and cardiomyopathy, anemia, weight gain and the use of antihypertensive drugs. Aim: this study aim to identify factors that affect the intradialysis hypotension of chronic kidney failure patients with hemodialysis. Method the uses the kind of quantitative with a cross-sectional study design, total sample of 296 hemodialysis patients. Data analysis using chi square test and coefficient correlation. Results showed a correlation between age and cardiovascular history with the incidence of intradialysis hypotension and while gender have nothing to do with the incidence of intradialysis hypotension. Conclusion monitoring needs to be improved while the patient is undergoing hemodialysis so as not to cause intradialysis hypotension which threatens the health and safety of the patient while undergoing hemodialysis.  Keywords: Chronic Kidney Diseases; Hemodialysis; Intradialysis Hypotension